A cross-sectional study of pulmonary and quality of life outcomes in patients with CABG and COPD - Cakirkose, Ozlem; Corut, Ruhsel; Muhtaroglu, Ali; Kuloglu, Ersin; Acar, Berkan (Frontiers in Medicine, 2026)
BackgroundPulmonary dysfunction and compromised respiratory quality of life are frequent sequelae in both coronary artery bypass grafting (CABG) patients and those with chronic obstructive pulmonary disease (COPD). In this study, we compared pulmonary function and respiratory-related quality of life between these two patient groups based on real-life clinical data.MethodsA total of 89 patients (42 CABG and 47 COPD) were assessed. Baseline demographics, body mass index (BMI), pulmonary function tests (FVC, FEV1, and FEV1/FVC), and St. George’s Respiratory Questionnaire (SGRQ) scores were compared. Comparisons between groups were made using t-tests and chi-squared tests. Correlation and multiple linear regression analyses identified determinants of FEV1 (%) and SGRQ total scores.ResultsThe groups were comparable in age and sex, but BMI was higher in the CABG group (p = 0.002). CABG patients demonstrated significantly better SGRQ total, symptom, and activity scores than COPD patients (p < 0.05). Pulmonary function was also superior in the CABG group for FVC (%), FEV1 (%), and FEV1/FVC (all p < 0.05). Correlation analyses revealed strong associations between lower SGRQ scores and better pulmonary function. A multiple regression analysis identified “group” (CABG vs. COPD) as the only significant predictor of both FEV1 (%) (β = −0.25, p = 0.032) and SGRQ total score (β = 0.29, p = 0.016).ConclusionPatients with prior CABG exhibit more favorable lung function and respiratory quality of life than COPD patients. Group status was independently associated with outcomes, suggesting that both groups need tailored rehabilitation and multidisciplinary management. Therefore, multicenter prospective studies are warranted.